The Investigation of Students Motivated Attitude Towards Podcast in Listening Comprehension - Siregar, Kezia Putri; Suryaman, Maman; Hakim, Putri Kamalia (Edukasiana: Jurnal Inovasi Pendidikan, 2026)
While podcasts have gained recognition as effective tools for developing EFL listening comprehension, the psychological and affective dimensions, particularly students' motivated attitudes, remain underexplored, especially in Indonesian contexts. This qualitative case study investigated three Indonesian tenth-grade students' motivated attitudes toward podcast-based listening instruction through questionnaires and semi-structured interviews analyzed using Braun and Clarke's reflexive thematic analysis. Findings revealed predominantly positive motivated attitudes characterized by enthusiasm, motivation, satisfaction, and willingness to recommend podcasts. Students perceived podcasts as highly effective for understanding diverse accents and authentic language. Three themes emerged: positive motivational responses, perceived learning benefits, and implementation challenges. Unexpectedly, divergent responses regarding confidence development suggested this dimension may follow different trajectories. Results align with Technology Acceptance Model and Self-Determination Theory, indicating that podcasts' perceived usefulness, authenticity, and autonomy-supportive characteristics enhance motivated attitudes. However, technical challenges and need for structured guidance highlight pedagogical scaffolding importance. This study contributes empirical evidence regarding affective dimensions mediating successful podcast integration in EFL contexts, offering insights for learner-responsive technology-enhanced instruction.